Supplementation of maize-based concentrates and milk production in indigenous cows (Bangladesh Veterinarian, 2010)
The effect of feeding maize-based concentrates on milk yield in cows with cost-benefit analysis was done at smallholder farms in four districts of northern Bangladesh. Concentrate mixtures containing wheat bran, rice polish and sesame oil cake were supplied to 40 indigenous (Desi) cows (20 in Group A and 20 in Group B) for 30 days before intervened feeding. Cows were given 1 kg maize-based concentrates/100 kg body weight twice daily for a further 60 days after feeding intervention. Cows' body weight, milk yield and farm income were recorded before and after maze-based concentrate supplementation. Milk production is increased by 30% for Group A and 90% for Group B. The difference in milk yield before and after supplementation of maize-based concentrate in Group B was significant (P